Patience of Job's Faith in Suffering and Relevance for Christians Today - Taso, Donatus Bhato; Boy, Mikhael Valens; Senda, Siprianus (Jurnal Ar Ro'is Mandalika (Armada), 2021)
The patience of the faith of the righteous in the face of suffering. The prototype of the patience of the righteous that we want to address is Job. The suffering that Job experienced is a picture of the suffering of a good and righteous man who fears evil. Job feared evil so much that he lived a life of obedience to God, but interestingly he still fell into a tremendous suffering. Job lost all his wealth, family and illnesses but he remained patient and always relied on God. In the face of various trials, Job accepted them willingly and did not make him angry and far from God. Job's patience in various trials is worthy to be emulated by humans in this era. Job's sufferings were sufferings where God wanted to test Job's faith and patience. Just as God tries the faith and patience of the righteous, God will return and restore Job's suffering by bestowing abundant blessings again.